Pengaruh E-Service Quality, Electronic Word Of Mouth, dan Price terhadap Purchase Decision pada Pengguna E-Commerce Lazada di Kota Bandung - Detria Aliifah Rifdah; Dedy Ansari Harahap; Mochamad Malik Akbar Rohandi (UNISBA Press, 2022)
Abstract. The development of information and communication technology today has brought changes to consumer behavior in shopping from offline to online, making it simpler for consumers to make decisions. Because the data shows a decrease in monthly web visitors, companies must overcome the decline and increase the number of visitors by utilizing e-service quality, electronic word of mouth, and price. The use of electronic word-of-mouth, price, and service quality to purchasing decisions is the main subject of this study. The study aims to determine the effect of E-Service Quality, Electronic Word Of Mouth, and Price on Costumer Purchase Decisions at Lazada E-Commerce in Bandung City. Data collection techniques in this study were carried out through the distribution of questionnaires. The object of this research is e-commerce in the city of Bandung with a sample of 400 consumers. The sampling technique used in this research is purvosive sampling. Analysis of the data used is descriptive and verification with quantitative methods. analysis using multiple linear regression analysis, T test and F test. The results of this study indicate that the E-Service Quality partially has a significant effect on Purchase Decisions, variable Electronic Word Of Mouth partially has a significant effect on Purchase Decisions, variable Price partially has a significant effect on Purchase Decisions. And simultaneously the variables of E-Service Quality, Electronic Word Of Mouth, and Price have a significant effect on Costumer Purchase Decisions at Lazada E-commerce in Bandung City. Abstrak. Perkembangan teknologi informasi dan komunikasi saat ini telah membawa perubahan pada perilaku konsumen dalam berbelanja dari offline ke online, sehingga terciptanya proses keputusan pembelian yang lebih mudah. Karena data menunjukkan adanya penurunan pengunjung web bulanan, perusahaan harus mengatasi penurunan dan meningkatkan jumlah pengunjung dengan memanfaatkan e-service quality, electronic word of mouth, dan price. Penelitian ini berfokus pada penerapan E-Service Quality, Electronic Word Of Mouth, dan Price terhadap Purchase Decision. Tujuan penelitian ini untuk mengetahui pengaruh E-Service Quality, Electronic Word Of Mouth, dan Price terhadap Purchase Decision pada pengguna E-Commerce Lazada. Teknik pengumpulan data dalam penelitian ini dilakukan melalui penyebaran kuesioner. Objek pada penelitian ini adalah pengguna e-commerce Lazada di Kota Bandung dengan sampel sebanyak 400 orang pengguna. Teknik sampling yang digunakan dalam penelitian ini adalah purvosive sampling. Analisis data yang digunakan adalah analisis deskriptif dan verifikatif dengan metode kuantitatif yaitu menggunakan analisis regresi linear berganda, uji T dan uji F. Hasil dari penelitian ini menunjukkan bahwa variabel E-Service Quality secara parsial berpengaruh signifikan terhadap Purchase Decision, variabel Electronic Word Of Mouth secara parsial berpengaruh signifikan terhadap Purchase Decision, variabel Price secara parsial berpengaruh signifikan terhadap Purchase Decision. Dan secara simultan variabel E-Service Quality, Electronic Word Of Mouth, dan Price berpengaruh signifikan terhadap Purchase Decision pada pengguna E-commerce Lazada di Kota Bandung.